The signalling channel of negative interest rates - Oliver De Groot; Alexander Haas (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Negative interest rates remain a controversial policy for central banks. We study a novel signalling channel and ask under what conditions negative rates should exist in an optimal policymaker's toolkit. We prove two necessary conditions for the optimality of negative rates: a time-consistent policy setting and a preference for policy smoothing. These conditions allow negative rates to signal policy easing, even with deposit rates constrained at zero. In an estimated model, the signalling channel dominates the costly interest margin channel. However, the effectiveness of negative rates depends sensitively on the degree of policy inertia, level of reserves, and ZLB duration.
Keywords: E44; E52; E61; 330; Monetary policy; Taylor rule; Forward guidance; Liquidity trap